Preparation method of porous organic carrier PtBuMA loaded nZVI adsorbent and application of porous organic carrier PtBuMA loaded nZVI adsorbent to adsorption of heavy metal ions in water
The modified PtBuMA-nZVI adsorbent addresses agglomeration and oxidation issues of nZVI, enhancing the removal of Cu(II), Zn(II), and As(III) ions in water through improved adsorption and redox capabilities.
Patent Information
- Application Number
- CN202411538192.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-13
AI Technical Summary
Existing methods for treating groundwater pollution with nano-zero-valent iron (nZVI) face issues such as agglomeration, oxidation, and poor adsorption selectivity, leading to reduced effectiveness in removing heavy metal ions like Cu(II), Zn(II), and As(III).
A method is developed to prepare a modified PtBuMA-loaded nZVI adsorbent by using tert-butyl methacrylate as a monomer to create a porous material with high surface area and functional groups, which stabilizes nZVI and enhances adsorption sites, reducing agglomeration and oxidation.
The modified PtBuMA-nZVI adsorbent effectively improves the removal of Cu(II), Zn(II), and As(III) ions in water by providing stable adsorption sites and strong redox capabilities, overcoming the limitations of traditional nZVI carriers.
Smart Images

Figure HDA0005112105180000011 
Figure HDA0005112105180000012 
Figure HDA0005112105180000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection, and in particular relates to a method for preparing a modified PtBuMA-loaded nZVI heavy metal ion adsorbent. Background Art
[0002] The toxicity of Cu(Ⅱ), Zn(Ⅱ) and As(Ⅲ) in groundwater will become stronger with time. These three ions will also migrate over time, causing a wider range of pollution. Therefore, it is urgent to seek an efficient treatment technology method.
[0003] Zero-valent iron has been studied and developed in the treatment of groundwater pollution in many countries and regions. Due to its extremely small particle size and high surface energy, it is easy to agglomerate particles during use, which affects the dispersion and activity of zero-valent iron and seriously affects its application value. In addition, if it is not properly stored, when zero-valent iron is exposed to oxygen, oxidation reaction will occur, forming an oxide coating on its surface, which hinders direct contact with pollutants.
[0004] Among them, in the existing technologies such as CN201110075207.1 A novel method for preparing loaded nano zero-valent iron, most of them load nano zero-valent iron on porous materials such as activated carbon, sepiolite, zeolite, etc. to improve the dispersibility of nano zero-valent iron. However, these carriers have shortcomings such as tending to be saturated after adsorbing heavy metal ions, poor adsorption selectivity for different heavy metal ions, and desorption of heavy metal ions from their surfaces after the reaction. At the same time, high-quality porous materials such as activated carbon, sepiolite, zeolite, etc. will also increase the preparation cost of nano zero-valent iron.
[0005] How to modify the surface of a carrier with high porosity and specific surface area so that it can provide adsorption sites for nano-zero-valent iron and change the surface activity of nano-zero-valent iron to reduce its agglomeration and oxidation, so as to obtain a PRB filler with both good adsorption capacity and redox ability, is the technical problem to be solved by the present invention. Summary of the invention
[0006] In order to solve the above problems, the present invention proposes a method for preparing a heavy metal ion adsorbent of modified PtBuMA loaded with nZVI. The prepared organic polymer has both high porosity and large specific surface area, and also has rich functional group sites on the surface to attach nano zero-valent iron as a filler for PRB.
[0007] The present invention adopts tert-butyl methacrylate (tBMA) as the monomer of organic porous material, because it is the monomer with the most branches and the smallest molecular weight. By utilizing this advantage, a porous material with low density, rich pore structure and large specific surface area, namely poly(t-Butyl Methacrylate), PtBuMA, can be made. These can provide a basis for the attachment of nZVI. In addition, since the organic polymer itself has a rich functional group structure, it is also easier to obtain functional groups through modification, and these functional groups themselves play a positive role in some adsorption or attachment of nZVI. As for PtBuMA, it itself has a large functional group modification potential, which can be attributed to the fact that each structural unit of itself contains a free ester group, which can become a carboxyl group after acidification and hydrolysis, which provides a large number of active sites for the adsorption of ions. In addition, these active sites can also provide adsorption sites for nZVI, which enables nZVI to better attach to the surface of PtBuMA.
[0008] The purpose of the present invention is to provide a new method for preparing a modified PtBuMA (poly tert-butyl methacrylate) loaded nZVI agent for removing copper, zinc and arsenic ions in water. The present invention reduces the problems of nZVI aggregation, oxidation and precipitate accumulation in the reaction by loading nZVI onto the surface of the modified PtBuMA, and at the same time achieves the purpose of efficiently removing Cu(II), Zn(II) and As(III) ions in water, so as to solve the problems existing in the prior art.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] S1. Preparation of emulsion of porous organic carrier PtBuMA: Add benzoyl peroxide initiator, crosslinker, tert-butyl methacrylate (TMPTA) monomer, pore-forming agent and emulsifier into a beaker to form an oil phase. Ultrasonicate for 5-10 minutes, then use an infusion tube to uniformly add the inner dispersed phase (deionized water) to the oil phase under stirring at 6000rpm in a homogenizer. After the addition is complete, stir at 4500rpm for 5 minutes to ensure that the emulsion is fully emulsified. Finally, add N,N-dimethylaniline, wait until the color of the emulsion turns lavender and no longer changes, stop stirring, and obtain the W / O initial emulsion.
[0011] The amount of benzoyl peroxide initiator used is 2-5% of the mass of tert-butyl methacrylate monomer; the crosslinking agent is trimethylolpropane triacrylate; and the amount of the crosslinking agent used in S1 is 30%-65% of the mass of tert-butyl methacrylate.
[0012] The pore-forming agent is toluene; the amount of the pore-forming agent is 50%-170% of the mass of tert-butyl methacrylate.
[0013] The emulsifier is PPP (PEG-PPG-PEG); the amount of the emulsifier is 12%-18% of the mass of tert-butyl methacrylate.
[0014] The volume ratio of deionized water to tert-butyl methacrylate is 4.25-5.16. The volume amount of N,N-dimethylaniline is 0.0442-0.0537 of the volume of deionized water.
[0015] The internal dispersed phase in S1 is deionized water, and the volume fraction of the internal dispersed phase (water) accounts for 52%-72% of the total volume of the internal dispersed phase and the oil phase.
[0016] S2, preparation of porous organic carrier PtBuMA: Weigh ammonium persulfate and polyvinyl alcohol and add them to deionized water. Pass nitrogen and heat the solution to 45°C while stirring at 300rpm. Wait for the ammonium persulfate and polyvinyl alcohol (PVA) to be completely dissolved, then quickly add the W / O initial emulsion of S1 into the flask, wait until the solution turns yellow-green, then add tetramethylethylenediamine and react for 15 minutes. After the reaction is completed, filter the suspension and wash it with methanol and deionized water at the same time to remove the emulsifier residue. Vacuum dry for 12 hours to obtain the PtBuMA carrier.
[0017] The mass ratio of ammonium persulfate to polyvinyl alcohol and tetramethylethylenediamine in S2 is 0.5-1:1:0.8-1, and the amount of ammonium persulfate is 5-10% of the mass of tert-butyl methacrylate. The volume ratio of the deionized water in step (2) to the deionized water in step (1) is 50-150:10.
[0018] S3. Modification of the porous organic carrier PtBuMA carrier: Take the PtBuMA carrier prepared in (2) and add trifluoroacetic acid and dichloromethane, and fill the flask with nitrogen intermittently (every hour). After the reaction is completed for 6 hours, the obtained sample is stirred and cleaned in a conical flask with dichloromethane in a water bath for 24 hours under light-proof conditions. The temperature is controlled at 20°C and the stirring speed is 100 rpm. After cleaning, vacuum dry at 50°C for 24 hours to obtain the hydrolyzed modified PtBuMA carrier.
[0019] The volume ratio of trifluoroacetic acid to dichloromethane in S3 was 1:10. The concentration of PtBuMA carrier in trifluoroacetic acid was 0.5 g / mL.
[0020] S4. Preparation of porous organic carrier modified PtBuMA loaded nZVI: FeSO4·7H2O, PEG, modified PtBuMA carrier and deionized water were weighed and mixed evenly, and ultrasonicated for 0.5h. Anhydrous ethanol was added thereto, and nitrogen was introduced, and stirred with a magnetic stirrer for 0.5h. Then, a 0.35mol / L NaBH4 aqueous solution was prepared and added dropwise to the above solution at a drop rate of one drop per 2 seconds, and the reaction was continued for 1.5h. After the reaction was completed, the solution was centrifuged at 8000rpm, and the obtained black particles were quickly washed with deionized water and anhydrous ethanol for 3 times, and freeze-dried for 24h to obtain porous organic carrier modified PtBuMA loaded nZVI (PtBuMA-nZVI).
[0021] The mass ratio of FeSO4·7H2O and PEG in S4 and the modified PtBuMA carrier is 5:2.5:2.
[0022] S5. Removal of Cu(Ⅱ), Zn(Ⅱ), and As(Ⅲ) ions in groundwater: The designed heavy metal solution simulation adopts an ion concentration 10 times that of Class V water in the Groundwater Quality Standard, that is, 1000ml of 15mg / L Cu(Ⅱ), 50mg / L Zn(Ⅱ), and 0.5mg / L As(Ⅲ) standard solutions are prepared as simulations of groundwater conditions. Adjust the pH to 5-9, take 1.0g of the modified PtBuMA-nZVI sample and add it to 1000ml of the solution, take a sample every 10 minutes, filter the sample through a 0.22μm vacuum filter, measure the concentration of copper, zinc, and arsenic ions in the filtrate by atomic absorption spectrometer, and calculate the removal rate of each metal ion.
[0023] The present invention designs a new nZVI carrier, PtBuMA, and modifies it on this basis so that its surface has more binding sites for adsorption, and then successfully loads nZVI on the modified PtBuMA carrier to obtain a "modified PtBuMA-nZVI" adsorption material, which realizes the efficient removal of Cu(Ⅱ), Zn(Ⅱ) and As(Ⅲ) ions in water. In addition, the hydrogen atoms in the carboxyl and hydroxyl groups on the surface of PtBuMA-nZVI will form hydrogen bonds with nZVI and stabilize nZVI at the same time, reduce the energy state of nZVI, thereby reducing the surface reactivity and agglomeration of nZVI, and also provide more active sites for nZVI, making the antioxidant capacity of nZVI stronger. Therefore, the modified PtBuMA loaded nZVI can efficiently in situ remediate Cu(Ⅱ), Zn(Ⅱ), and As(Ⅲ) in groundwater.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The modified PtBuMA-nZVI material designed in the present invention can effectively improve the agglomeration problem of nZVI and provide a large number of active sites for the adsorption of copper, zinc and arsenic ions, which can effectively remove copper, zinc and arsenic ions in groundwater.
[0026] (2) The surface of the modified PtBuMA-nZVI material designed by the present invention is rich in carboxyl and hydroxyl groups, which results in Fe 0 First react with metal ions, then react with oxygen in the air, hydroxyl and carboxyl groups react by changing Fe 0 The order of gaining and losing electrons between oxygen and metal ions ensures that Fe 0 Reducing ability of metal ions.
[0027] (3) The tert-butyl methacrylate (tBMA) used in the present invention as the monomer of the organic porous material has the most branches and the smallest molecular weight, and can be used to make a porous material with low density, rich pore structure and large specific surface area - poly (t-Butyl Methacrylate) (PtBuMA).
[0028] (4) PtBuMA has a rich functional group structure and is easier to obtain functional groups through modification. These functional groups themselves play a positive role in some adsorption or attachment of nZVI. At the same time, each structural unit of PtBuMA contains a free ester group, which can become a carboxyl group after acidification and hydrolysis, allowing nZVI to better adhere to the surface of PtBuMA. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0030] Figure 1 This is a flow chart of the preparation process of the emulsion of the porous organic carrier PtBuMA.
[0031] Figure 2 This is a flow chart of the preparation process of the porous organic carrier PtBuMA.
[0032] Figure 3 Photos of PtBuMA prepared with different volume fractions of the dispersed phase (water).
[0033] Figure 4SEM images of PtBuMA prepared with different mass fractions of emulsifier: (a) 0.2857 g; (b) 0.300 g; (c) 0.3186 g.
[0034] Figure 5 SEM images of PtBuMA prepared with different volumes of cross-linking agent: (a) 1.1 ml; (b) 0.9 ml; (c) 0.7 ml.
[0035] Figure 6 This is the nitrogen desorption curve of the PtBuMA carrier prepared with different volumes of cross-linking agent.
[0036] Figure 7 SEM images of PtBuMA prepared with different volumes of pore-forming agent: (a) 1.15 ml; (b) 2.30 ml; (c) 3.44 ml.
[0037] Figure 8 SEM images of PtBuMA prepared with different volumes of the third phase (water): (a) 50 ml; (b) 100 ml; (c) 150 ml.
[0038] Fig. 9 SEM images of PtBuMA prepared with different dispersant (PVA) dosages: (a) 0.1563 g; (b) 0.2083 g; (c) 0.2604 g.
[0039] Fig.10 SEM images of PtBuMA at different suspension stirring speeds: (a) 250 rpm; (b) 300 rpm; (c) 350 rpm; (d) 400 rpm; (e) 450 rpm.
[0040] Fig.11 This is the SEM image of the PtBuMA carrier obtained under the conditions of Example 1.
[0041] Fig.12 This is the nitrogen adsorption-desorption curve of the PtBuMA carrier obtained under the conditions of Example 1.
[0042] Fig.13 Schematic diagram of the hydrolysis modification process of the porous organic carrier PtBuMA.
[0043] Fig.14 This is the infrared characterization image of the modified porous organic support PtBuMA.
[0044] Fig.15 This is the process flow chart for loading nZVI on the modified porous organic carrier PtBuMA.
[0045] Fig.16 SEM-EDS image of nZVI loaded on the modified porous organic carrier PtBuMA.
[0046] Fig.17 XRD patterns of nZVI (a) and modified PtBuMA-nZVI adsorption materials (b-2 days, c-4 days, d-6 days).
[0047] Fig.18 XPS graph of modified PtBuMA-nZVI prepared by hydrolysis modification of PtBuMA for different times.
[0048] Fig.19 This graph shows the effect of different initial concentrations of metal ions on the removal of Cu(II), Zn(II), and As(III) by modified PtBuMA-nZVI. DETAILED DESCRIPTION
[0049] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0050] Example 1
[0051] Add 0.048g of benzoyl peroxide, 2.06ml of tert-butyl methacrylate, 0.7ml of crosslinking agent trimethylolpropane triacrylate, 2.30ml of pore-forming agent toluene and 0.3g of emulsifier PPP into a beaker to form an oil phase. Ultrasonicate for 5-10 minutes, then add 10ml of deionized water (66% by volume) to the oil phase at a uniform speed through an infusion tube under 6000rpm stirring of a homogenizer. After the addition is complete, stir at 4500rpm for 5 minutes to ensure that the emulsion is fully emulsified. Finally, add 0.47ml of N,N-dimethylaniline, wait until the color of the emulsion turns lavender and no longer changes, stop stirring, and obtain a W / O initial emulsion.
[0052] Weigh 0.15g of ammonium persulfate and 0.15g of polyvinyl alcohol and add them to 50mL of deionized water (third phase (water)). Pass nitrogen to obtain a suspension, heat the suspension to 45°C and stir at 300rpm. Wait for the ammonium persulfate and polyvinyl alcohol (PVA) dispersant to be completely dissolved, then quickly add the W / O initial emulsion to the flask, wait until the solution turns yellow-green, then add 0.18ml of tetramethylethylenediamine and react for 15min. After the reaction is completed, filter the suspension and wash it with methanol and deionized water at the same time to remove the emulsifier residue. Vacuum dry for 12h to obtain the PtBuMA carrier.
[0053] Example 2
[0054] The difference between this embodiment and embodiment 1 is that the amount of deionized water added is different, so that the volume fraction of the inner dispersed phase (water) is 52%, and the remaining steps are the same as those in embodiment 1.
[0055] Example 3
[0056] The difference between this embodiment and embodiment 1 is that the amount of deionized water added is different, so that the volume fraction of the inner dispersed phase (water) is 59%, and the remaining steps are the same as those in embodiment 1.
[0057] Example 4
[0058] The difference between this embodiment and embodiment 1 is that the amount of deionized water added is different, so that the volume fraction of the inner dispersed phase (water) is 72%, and the remaining steps are the same as those in embodiment 1.
[0059] Figure 3 (a1, a2, a3) are photos of the PtBuMA emulsion after drying, which was prepared when the volume fraction of the internal dispersed phase (water) was 52%. However, it did not form after drying and filtration, and scanning electron microscopy could not be taken. Figure 3 (b1, b2) are scanning electron micrographs of the carrier prepared when the volume fraction of the internal dispersed phase (water) is 59%. Figure 3 (c1, c2) are scanning electron micrographs of the carrier prepared when the volume fraction of the internal dispersed phase (water) is 66%. Figure 3 d is an emulsion prepared with an internal dispersed phase (water) volume fraction of 72%. The emulsion is too concentrated and the PtBuMA carrier cannot be prepared.
[0060] from Figure 3 It can be seen from a that when the volume fraction of the internal dispersed phase (water) is 52%, only irregularly shaped particles remain after the emulsion is filtered and dried, and the carrier is not formed. It is speculated that this may be because the volume fraction of the internal dispersed phase in the emulsion is too low, resulting in a decrease in the viscosity coefficient of the emulsion, so it is not fully formed. Figure 3 a to Figure 3 b It can be seen that when the volume fraction of the inner dispersed phase increases, the PtBuMA carrier has a regular structure, which further proves that Figure 3 The reason for this is that the volume fraction of the internal dispersed phase is too low, the viscosity coefficient of the emulsion is too low, and the carrier is difficult to form. Figure 3 It can be clearly seen from b2 that when the volume fraction of the inner dispersed phase is 59%, although the overall structure of the carrier is formed, the skeleton structure is very unstable and there are many damages, which is still caused by the insufficient viscosity coefficient of the emulsion. Figure 3 b to Figure 3 c, we can observe that Figure 3 c not only has a regular spherical structure, but also has a more stable skeleton structure. At the same time, the diameter of the carrier has become nearly doubled, and the pore structure has become more complex. Figure 3The beaker in d is a concentrated emulsion prepared at a volume fraction of 72% of the internal dispersed phase. At this time, the concentrated emulsion becomes very viscous and gradually turns into a jelly-like state or even hardens after being left for 1 minute. This further proves the important influence of the volume fraction of the internal dispersed phase on the entire emulsion state and the final carrier structure. In the subsequent examples, the volume fraction of the internal dispersed phase (water) is set to 66%.
[0061] Example 5
[0062] The difference between this embodiment and embodiment 1 is that the amount of emulsifier PPP used is 0.2857 g, and the remaining steps are the same as those in embodiment 1.
[0063] Example 6
[0064] The difference between this embodiment and embodiment 1 is that the amount of emulsifier PPP used is 0.3186 g, and the remaining steps are the same as those in embodiment 1.
[0065] Figure 4 The SEM images of PtBuMA prepared with different emulsifier weights: (a) 0.2857 g; (b) 0.3000 g; (c) 0.3186 g. Figure 4 From a1 to b1, it can be seen that the overall structure of the PtBuMA carrier has become more regular. The surface of the carrier in a1 is still relatively "rough", while the surface of the carrier in b1 is almost complete and the overall sphericity is also higher. From b1 to c1, it can be seen that the sphericity of the PtBuMA carrier is still high, but there are more "bumps" on the surface of the c1 carrier, and even two carriers are connected. This is because when the amount of emulsifier is small, although the emulsion system can be formed, due to the instability of the system, there are more "imperfect" carriers such as a1; when the amount of emulsifier is too much, the excess emulsifier will form too many micelles, which will destroy the balance of the emulsion system. Therefore, the carrier structure has "bumps" and connections appear between the carriers. In the subsequent examples, an emulsifier with a mass of 0.3g was selected to continue the experiment.
[0066] Example 7
[0067] The difference between this embodiment and embodiment 1 is that the amount of cross-linking agent trimethylolpropane triacrylate used is 0.9 ml, and the remaining steps are the same as those in embodiment 1.
[0068] Example 8
[0069] The difference between this embodiment and embodiment 1 is that the amount of cross-linking agent trimethylolpropane triacrylate used is 1.1 ml, and the remaining steps are the same as those in embodiment 1.
[0070] from Figure 5It can be seen that the structures of the PtBuMA carriers prepared by 1.1ml, 0.9ml and 0.7ml of cross-linking agent are almost the same, and the internal pores are evenly distributed. Therefore, it is concluded that the cross-linking agent has little effect on the overall structure of the entire PtBuMA carrier, but with the reduction of cross-linking agent, the pore size of the internal pore structure gradually increases.
[0071] Figure 6 It shows that when the volume of the cross-linking agent is 0.7 ml, the nitrogen desorption efficiency of PtBuMA is the best. Therefore, in the subsequent examples, a cross-linking agent dosage of 0.7 ml is selected.
[0072] Example 9
[0073] The difference between this embodiment and embodiment 1 is that the amount of pore-forming agent toluene used is 1.15 ml, and the remaining steps are the same as those in embodiment 1.
[0074] Example 10
[0075] The difference between this embodiment and embodiment 1 is that the amount of pore-forming agent toluene used is 3.44 ml, and the remaining steps are the same as those in embodiment 1.
[0076] from Figure 7 It can be seen that with the increase of the pore-forming agent dosage, the pore size of the PtBuMA carrier becomes significantly larger and gradually damaged. At the same time, it can be observed from a2 to b2 to c2 that the pore size distribution of the carrier becomes more uneven, from 0.5-1μm in a2 at the beginning, to 0.5-3μm in b2, and then to 0.5-4μm in c2. In the subsequent examples, b2 with a pore size distribution of 0.5-3μm is the most suitable, because it has a larger pore structure than a2, and a more uniform and stable pore structure than c2. Therefore, in the subsequent examples, a pore-forming agent dosage of 2.30ml is selected.
[0077] Embodiment 11
[0078] The difference between this embodiment and embodiment 1 is that the amount of the third phase (water) is 100 ml, and the remaining steps are the same as those in embodiment 1.
[0079] Example 12
[0080] The difference between this embodiment and embodiment 1 is that the amount of the third phase (water) is 150 ml, and the remaining steps are the same as those in embodiment 1.
[0081] Depend on Figure 8It can be seen that when the volume of the third phase (water) is 50ml, 100ml and 150ml, PtBuMA carriers can be prepared, and the carriers at the three volumes have a good regular overall structure. However, as the volume of the third phase (water) increases, the number of pores on the carrier surface decreases and the pore size becomes larger. When the volume of the third phase (water) is 100mL, the surface of the carrier is damaged to varying degrees. This may be because when the volume of the third phase (water) increases, excessive water causes the interface forces between the suspension system and the concentrated emulsion system to become more and stronger. When the emulsion forms a carrier, the surface is acted upon by more forces, resulting in damage to the carrier surface. Figure 8 From a2, b2 and c2, it can be seen that the internal structure of the PtBuMA carrier is almost intact, with only some pore structures broken. It can be seen that the volume of the third phase (water) in the suspension system has a significant effect on the surface structure of PtBuMA. Therefore, in the subsequent examples, a volume of 50 ml of the third phase water will be mainly used to prepare the PtBuMA carrier.
[0082] Example 13
[0083] The difference between this embodiment and embodiment 1 is that the amount of PVA used is 0.2083 g, and the remaining steps are the same as those in embodiment 1.
[0084] Embodiment 14
[0085] The difference between this embodiment and embodiment 1 is that the amount of PVA used is 0.2604 g, and the remaining steps are the same as those in embodiment 1.
[0086] Fig. 9 The following are scanning electron micrographs of PtBuMA prepared with different dispersant (PVA) dosages (a: 0.1563 g; b: 0.2083 g; c: 0.2604 g). It can be seen that at different PVA contents, the carrier has a relatively complete structure, and the pore structure inside the carrier is also relatively intact, with a relatively even distribution of pore sizes. Fig. 9 From a1-c1, we can see that the overall diameter of the carrier is gradually increasing. The pore size is roughly distributed in the range of 1-3 μm. Fig. 9From a2 to c2, it can be seen that the distribution of pore sizes has a trend of increasing. In a2, there are more pores of about 1μm, and only a few pores of about 3μm; in b2, there are more pores of about 3μm; in c3, the pores of about 3μm have exceeded 50%, and even several pores of about 4μm have appeared. This phenomenon occurs because when the dispersant (PVA) increases, the oil-water interface of the emulsion droplets becomes more stable, which makes the entire emulsion system more stable. When the dispersant (PVA) content is 0.2604g, the PtBuMA carrier has a larger diameter, but the number of pores under the electron microscope photos of the same magnification is equivalent to 0.1563g and 0.2083g, which indicates that when the dispersant (PVA) content is 0.2604g, the PtBuMA carrier has a richer internal pore structure. Larger pores and richer pore structures provide more sites for the subsequent attachment of nZVI, and at the same time provide more sites for the adsorption of Cu(Ⅱ), Zn(Ⅱ) and As(Ⅲ). Therefore, in the subsequent examples, the amount of PVA was set to 0.2604 g to prepare the PtBuMA carrier.
[0087] Embodiment 15
[0088] The difference between this embodiment and embodiment 1 is that the stirring speed of the suspension is 250 rpm, and the remaining steps are the same as those in embodiment 1.
[0089] Example 16
[0090] The difference between this embodiment and embodiment 1 is that the stirring speed of the suspension is 350 rpm, and the remaining steps are the same as those in embodiment 1.
[0091] Embodiment 17
[0092] The difference between this embodiment and embodiment 1 is that the stirring speed of the suspension is 400 rpm, and the remaining steps are the same as those in embodiment 1.
[0093] Embodiment 18
[0094] The difference between this embodiment and embodiment 1 is that the stirring speed of the suspension is 450 rpm, and the remaining steps are the same as those in embodiment 1.
[0095] Fig.10 The SEM images of PtBuMA at different stirring speeds (a: 250 rpm; b: 300 rpm; c: 350 rpm; d: 400 rpm; e: 450 rpm). Fig.10 a1 and b1. The structure of the PtBuMA support is rod-like or irregular in shape, which is due to the low stirring speed and poor sphericity of the polymer. Fig.10a2 and b2 also show that the pore structure of the entire interior is also disordered and dense, with a pore size of less than 1 μm. However, it can also be seen that from a1 to b1, the structure of the PtBuMA carrier is gradually becoming regular, and from a2 to b2, the internal pore structure is also gradually becoming regular and orderly. Fig.10 At c1, the structure of the entire PtBuMA carrier tends to be regular and stable, and the internal pore structure is also very regular, with almost no skeleton breakage. From c1 to d1, the structure of the PtBuMA carrier becomes irregular again, and some carriers lose their original spherical structure. The pore size on the surface and inside of the carrier increases, and some skeletons are damaged. This is because the excessive stirring speed makes the emulsion system unstable, and the carrier structure is damaged after the polymerization of the carrier is completed. Fig.10 e1 and e2 further show that excessive stirring speed will have a greater impact on the existing stable emulsion system. At the same time, we can observe that from a to b to c, the diameter of the carrier with a certain regular structure is slowly increasing, from less than 50 μm to 80-100 μm; from c to d to e, the overall carrier diameter is gradually decreasing, and finally only about 20 μm, which shows that the suspension stirring speed also has a certain effect on the size of the PtBuMA carrier. Therefore, in the subsequent examples, the suspension stirring speed will be set to 300 rpm to prepare the PtBuMA carrier.
[0096] Embodiment 19
[0097] Take 5g of the PtBuMA carrier prepared in Example 1 and add it to 10ml of trifluoroacetic acid and 100ml of dichloromethane, and fill the flask with nitrogen intermittently (every hour). After the reaction is completed for 6h, the obtained sample is stirred and cleaned in a conical flask with 50ml of dichloromethane in a water bath for 24h under light-proof conditions. The temperature is controlled at 20°C and the stirring speed is 100rpm. After cleaning, vacuum dry at 50°C for 24h to obtain the hydrolyzed modified PtBuMA carrier.
[0098] Weigh 5g FeSO4·7H2O, 2.5g PEG, 2g modified PtBuMA carrier and 50ml deionized water, mix evenly, and ultrasonicate for 0.5h. Add 30ml anhydrous ethanol, introduce nitrogen, and stir with a magnetic stirrer for 0.5h. Then, prepare 0.35mol / L NaBH4 aqueous solution, add it dropwise to the above solution at a drop rate of 2 seconds, and continue to react for 1.5h. After the reaction, the solution is centrifuged at 8000rpm, and the obtained black particles are quickly washed with deionized water and anhydrous ethanol for 3 times, and freeze-dried for 24h to obtain porous organic carrier modified PtBuMA loaded nZVI (PtBuMA-nZVI).
[0099] The designed heavy metal solution simulation uses an ion concentration 10 times that of Class V water in the Groundwater Quality Standard, that is, 1000 ml of 15 mg / L Cu(II), 50 mg / L Zn(II) and 0.5 mg / L As(III) standard solutions are prepared as simulations of groundwater conditions. The pH is adjusted to 5, 1.0 g of modified PtBuMA-nZVI sample is added, and the supernatant is sampled after reaching reaction equilibrium (90 min). The sample is filtered through a 0.22 μm vacuum filter, and the concentrations of Cu(II), Zn(II) and As(III) in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0100] Fig.13 Figure 1 is the infrared spectrum of the PtBuMA carrier before and after modification. Figure a is the infrared spectrum of the unmodified PtBuMA carrier. -1 、1260.53cm -1 The stretching vibration peak of the ester group (COC) is at 1732.77cm -1 The characteristic absorption peak of ester carbonyl is at 1368.36cm -1 The stretching vibration peak of tert-butyl-C(-CH3)3 is at 2940.63cm -1 and 2980.11cm -1 The stretching vibration peak of methyl (-CH3) is at b, c, and d are the infrared spectra of the PtBuMA carrier after hydrolysis for 2 days, 4 days, and 6 days, respectively. Comparing the peaks of the ester carbonyl in a and d, it can be seen that there is a significant shift, and the bond energy of the ester carbonyl has weakened, indicating that the reaction has occurred. In addition, the stretching vibration peaks of tert-butyl -C(-CH3)3 and methyl (-CH3) are weakened, and the peak at 3000.00cm -1 3500.00cm -1 The spectral band becomes stronger, which is the characteristic area of carboxyl hydroxyl group, indicating that the PtBuMA carrier is successfully hydrolyzed and modified, providing more active sites for the subsequent attachment of nZVI.
[0101] Embodiment 20
[0102] The difference between this embodiment and embodiment 19 is that before the reaction starts, the pH is adjusted to 6, and the remaining steps are the same as those in embodiment 1. 1.0 g of the modified PtBuMA-nZVI sample is added, and after the reaction equilibrium is reached, the supernatant is sampled, and the sample is filtered through a 0.22 μm vacuum filter, and the concentrations of Cu(II), Zn(II), and As(III) ions in the filtrate are measured by an atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0103] Embodiment 21
[0104] The difference between this embodiment and embodiment 19 is that before the reaction starts, the pH is adjusted to 7, and the remaining steps are the same as those in embodiment 1. 1.0 g of the modified PtBuMA-nZVI sample is added, and after the reaction equilibrium is reached, the supernatant is sampled, and the sample is filtered through a 0.22 μm vacuum filter, and the concentrations of Cu(II), Zn(II), and As(III) ions in the filtrate are measured by an atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0105] Embodiment 22
[0106] The difference between this comparative example and Example 19 is that before the reaction starts, the pH is adjusted to 8, and the remaining steps are the same as Example 1. 1.0 g of the modified PtBuMA-nZVI sample is added, and after the reaction equilibrium is reached, the supernatant is sampled, and the sample is filtered through a 0.22 μm vacuum filter. The concentrations of Cu(II), Zn(II), and As(III) ions in the filtrate are measured by an atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0107] Embodiment 23
[0108] The difference between this comparative example and Example 19 is that before the reaction starts, the pH is adjusted to 9, and the remaining steps are the same as Example 1. 1.0 g of the modified PtBuMA-nZVI sample is added, and after reaching the reaction equilibrium, the supernatant is sampled, and the sample is filtered through a 0.22 μm vacuum filter. The concentrations of Cu(II), Zn(II), and As(III) ions in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0109] Comparative Example 1
[0110] The difference between this comparative example and Example 19 is that before the reaction starts, 1 g of unloaded pure nZVI is added as the reagent, and the remaining steps are the same as those in Example 1. After reaching the reaction equilibrium, the supernatant is sampled, the sample is filtered through a 0.22 μm vacuum filter, and the concentrations of Cu(II), Zn(II), and As(III) ions in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0111] Comparative Example 2
[0112] The difference between this comparative example and Example 19 is that before the reaction starts, 1 g of unadjusted modified pure PtBuMA carrier is added as the reagent, and the remaining steps are the same as those in Example 1. After reaching the reaction equilibrium, the supernatant is sampled, the sample is filtered through a 0.22 μm vacuum filter, and the concentrations of Cu(II), Zn(II), and As(III) ions in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0113] Comparative Example 3
[0114] The difference between this comparative example and Example 19 is that before the reaction starts, 1 g of unadjusted modified PtBuMA-nZVI is added, and the remaining steps are the same as those in Example 1. After reaching the reaction equilibrium, the supernatant is sampled, the sample is filtered through a 0.22 μm vacuum filter, and the concentrations of Cu(II), Zn(II), and As(III) ions in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0115] Table 1 Effect of different solution pH on the removal of Cu(II), Zn(II) and As(III) by modified PtBuMA-nZVI and comparison of the removal of Cu(II), Zn(II) and As(III) by different materials
[0116] Cu(II) removal rate / % Zn(II) removal rate / % As(III) removal rate / % Embodiment 19 96.01 94.87 87.64 Embodiment 20 97.4 95.34 83.18 Embodiment 21 93.11 90.3 81.99 Embodiment 22 78.27 80.52 75.12 Embodiment 23 73.56 75.19 73.44 Comparative Example 1 44.29 41.34 26.23 Comparative Example 2 63.33 61.34 20.23 Comparative Example 3 78.03 76.34 66.15
[0117] As can be seen from Table 1, for Cu(II) ions, the maximum removal rates of nZVI, PtBuMA, unadjusted modified PtBuMA-nZVI and modified PtBuMA-nZVI after reaction equilibrium are 44.29%, 63.33%, 78.03% and 97.4%, respectively; for Zn(II) ions, the maximum removal rates of nZVI, PtBuMA, PtBuMA-nZVI and modified PtBuMA-nZVI are 41.34%, 61.34%, 76.34% and 95.34%, respectively; for As(III) ions, the maximum removal rates of nZVI, PtBuMA, PtBuMA-nZVI and modified PtBuMA-nZVI are 26.23%, 20.23%, 66.15% and 87.64%, respectively. When nZVI is used alone, the oxidation and agglomeration of nZVI particles greatly affect the degradation efficiency of nZVI. Therefore, no matter what kind of ion, the degradation rate of nZVI is not high. PtBuMA itself has a rich porous structure, which has good adsorption performance. It has a large number of (-O=COC=O-) structures on its surface. The carboxyl group in the ester group attracts metal ions to form a metal ester complex. Then the water molecules will attack the carbonyl group in the ester group, which will promote the decomposition of the ester into alcohol and carboxylic acid. The metal ions will react with the hydroxyl and carboxyl groups to complete the adsorption of Cu(II) and Zn(II). However, PtBuMA has the lowest removal rate for As(III). This is because As(III) does not react with certain groups in PtBuMA under normal circumstances. Most of the adsorption of As(III) by PtBuMA is physical adsorption. For PtBuMA-nZVI and modified PtBuMA-nZVI, it can be seen from Table 1 that the removal rate of the three ions of nZVI loaded on the modified PtBuMA carrier is significantly higher than that of the unmodified one. This is because the modified PtBuMA carrier has more carboxyl and hydroxyl groups, which can provide more active sites for nZVI. The presence of these active sites can reduce the surface reactivity of nZVI, thereby reducing the agglomeration of nZVI. In addition, due to the presence of hydroxyl and carboxyl groups, the reaction order of nZVI with O2 and metal ions is changed, thereby avoiding the loss of reducibility of nZVI due to corrosion.
[0118] Embodiment 24
[0119] The difference between this embodiment and embodiment 19 is that before the reaction starts, the dosage of modified PtBuMA-nZVI is adjusted to 0.5 g, and the remaining steps are the same as those in embodiment 1. After reaching the reaction equilibrium, the supernatant is sampled, the sample is filtered through a 0.22 μm vacuum filter, the concentrations of copper, zinc, and arsenic ions in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0120] Embodiment 25
[0121] The difference between this embodiment and embodiment 19 is that before the reaction starts, the dosage of modified PtBuMA-nZVI is adjusted to 1.5 g, and the remaining steps are the same as those in embodiment 1. After reaching the reaction equilibrium, the supernatant is sampled, the sample is filtered through a 0.22 μm vacuum filter, the concentrations of copper, zinc, and arsenic ions in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0122] Table 2 Effect of different dosages of modified PtBuMA-nZVI on the removal of Cu(II), Zn(II) and As(III)
[0123] Cu(II) removal rate / % Zn(II) removal rate / % As(III) removal rate / % Embodiment 19 96.01 94.87 81.43 Embodiment 24 91.62 90.51 71.99 Embodiment 25 98.5 96.36 87.64
[0124] As shown in Table 2, different dosages have a certain effect on the removal of Cu(II), Zn(II), and As(III) ions in the solution by modified PtBuMA-nZVI. For Cu(II), the removal rates of 0.5g, 1.0g, and 1.5g dosages are 91.62%, 91.62%, and 98.5%, respectively; for Zn(II), the removal rates of 0.5g, 1.0g, and 1.5g dosages are 90.51%, 94.87%, and 96.36%, respectively; for As(III), the removal rates of 0.5g, 1.0g, and 1.5g dosages are 71.99%, 81.43%, and 87.64%, respectively. It can be seen that the removal rate when the dosage is 0.5g is quite different from the removal rates of 1.0g and 1.5g. This may be because the 0.5g modified PtBuMA-nZVI added has reached adsorption equilibrium, so after reaching a certain removal rate, the removal effect of metal ions becomes worse; it may also be that the increase in dosage means an increase in the collision between the modified PtBuMA-nZVI and the ions, which affects the efficiency of adsorption and removal of heavy metal ions to a certain extent. When the dosage is 1.0g and 1.5g, Cu(II) and Zn(II) in the solution are almost completely removed, but the removal efficiency of As(III) is less than 90%. In addition, although the increase in dosage will increase the maximum adsorption amount and adsorption efficiency of the modified PtBuMA-nZVI, it should be noted that the most appropriate dosage should be selected to avoid material waste and secondary pollution. Therefore, the subsequent examples select the modified PtBuMA-nZVI dosage of 1.0g.
[0125] Embodiment 26
[0126] The difference between this embodiment and embodiment 19 is that before the reaction starts, the initial concentrations of Cu(II), Zn(II) and As(III) are adjusted to 7.5 mg / L, 25 mg / L and 0.25 mg / L, respectively, and the remaining steps are the same as those in embodiment 1. 1.0 g of the modified PtBuMA-nZVI sample is added, and after the reaction equilibrium is reached, the supernatant is sampled, the sample is filtered through a 0.22 μm vacuum filter, and the concentrations of Cu(II), Zn(II) and As(III) ions in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0127] Embodiment 27
[0128] The difference between this embodiment and embodiment 19 is that before the reaction starts, the initial concentrations of Cu(II), Zn(II) and As(III) are adjusted to 22.5 mg / L, 75 mg / L and 0.75 mg / L, respectively, and the remaining steps are the same as those of embodiment 20. 1.0 g of the modified PtBuMA-nZVI sample is added, and after the reaction equilibrium is reached, the supernatant is sampled, the sample is filtered through a 0.22 μm vacuum filter, and the concentrations of Cu(II), Zn(II) and As(III) ions in the filtrate are measured by atomic absorption spectrometer, and the removal rate of each metal ion is calculated.
[0129] Table 3 Effects of different initial concentrations of metal ions on the removal of Cu(II), Zn(II) and As(III) by modified PtBuMA-nZVI
[0130] Cu(II) removal rate / % Zn(II) removal rate / % As(III) removal rate / % Embodiment 19 96.01 94.87 87.64 Embodiment 26 99.13 96.79 90.13 Embodiment 27 88.19 85.44 82.12
[0131] As shown in Table 3, for Cu(II), when the initial concentration is 7.5 mg / L and 15 mg / L, the removal rate of copper ions by modified PtBuMA-nZVI is more than 95%, and when the initial concentration is 22.5 mg / L, the removal rate decreases. This is because when the ion concentration is low, the adsorption sites on the surface of modified PtBuMA-nZVI are sufficient for Cu(II) adsorption, so most of Cu(II) can be removed quickly. For Zn(II), the removal rates were high when the initial concentrations were 25 mg / L and 50 mg / L, but decreased when the initial concentration was 75 mg / L. This is because when the ion concentration was low, the adsorption sites on the surface of the modified PtBuMA-nZVI were sufficient to provide Zn(II) adsorption, so most of the Zn(II) could be removed quickly. When the ion concentration was too high, the adsorption sites on the surface of the modified PtBuMA-nZVI were insufficient to provide Zn(II). For As(III) ions, because there were enough surface active sites on the surface of the modified PtBuMA-nZVI at the beginning, and there were already some Fe 3+The surface of modified PtBuMA-nZVI can directly react with oxidized As(III). 3+ is consumed, and Fe in the solution 3+ However, for the initial concentration of 0.5 mg / L, there was also a "crowding out" phenomenon between more As(III) ions, which indicates that when the ion concentration increases further, the "crowding out" phenomenon between ions becomes more serious and the removal rate is further reduced.
[0132] Fig.16 This is the SEM-EDS image of nZVI loaded on the modified porous organic carrier PtBuMA. The nZVI in the modified PtBuMA-nZVI adsorption material did not show agglomeration. It is speculated that there are several possibilities: 1. Since nZVI particles have a small size, the action distance of the van der Waals force is very short, so the particles are affected by the van der Waals force and are easily attracted to each other and close to each other; 2. Since nZVI has a large specific surface area, it is in a high energy state and has a high chemical reactivity, so it is very easy to agglomerate. However, the hydrogen atoms in the hydroxyl group will form hydrogen bonds with nZVI. On the one hand, this stabilizes nZVI through hydrogen bonds, and on the other hand, the formation of hydrogen bonds consumes part of the energy, reducing the energy state of nZVI, thereby reducing the surface reactivity of nZVI and reducing agglomeration.
[0133] Fig.17 XRD patterns of nZVI (a) and modified PtBuMA-nZVI adsorption materials (b-2 days, c-4 days, d-6 days). It can be seen that the peak intensity of iron oxide when nZVI exists alone is stronger than that of the modified carrier, which indicates that the carboxyl and hydroxyl groups added by the modification play a role in providing more active sites for nZVI and reducing Fe 0 of oxidation.
[0134] Fig.18 The XPS graphs of modified PtBuMA-nZVI prepared by hydrolysis modification of PtBuMA at different times. The peak area ratio of XPS can also more intuitively show that as the hydrolysis modification time increases, the carboxyl hydroxyl groups also increase, providing more active sites for nZVI, which makes Fe 0 The antioxidant capacity of vitamin C becomes stronger, and the total content proportion increases.
[0135] Fig.19The figure shows the effect of different initial concentrations of metal ions on the removal of Cu(II), Zn(II), and As(III) by modified PtBuMA-nZVI. As can be seen from the figure, when the reaction was carried out for 90 minutes, the concentrations of Cu(II), Zn(II), and As(III) ions in the solution did not change, which indicates that the modified PtBuMA-nZVI has largely overcome the deficiency of heavy metal ions desorption from its surface after the reaction.
[0136] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a porous organic carrier PtBuMA loaded nZVI adsorbent, characterized in that: The specific preparation steps are as follows: (1) Preparation of an emulsion of a porous organic carrier PtBuMA: an initiator, tert-butyl methacrylate monomer, a crosslinking agent, a pore-forming agent and an emulsifier are mixed to form an oil phase. Under stirring in a homogenizer, an aqueous phase is added dropwise to the oil phase. The volume fraction of the aqueous phase is 52%-72%. After the addition is completed, the emulsion is fully emulsified. Finally, a stabilizer is added. The color of the emulsion no longer changes, and stirring is stopped to obtain a W / O initial emulsion. (2) Preparation of porous organic carrier PtBuMA: weigh initiator and dispersant and add them to deionized water, introduce nitrogen, heat and stir the solution to dissolve, obtain suspension, stir at 250-450 rpm, then add W / O initial emulsion obtained in step (1) to the suspension, wait until the solution turns yellow-green, then add crosslinking agent to react, after the reaction, filter the suspension, wash, and dry to obtain porous PtBuMA carrier; (3) Modification of the porous organic carrier PtBuMA carrier: The porous PtBuMA carrier obtained in (2) is added to a mixed solution of trifluoroacetic acid and dichloromethane, and nitrogen is intermittently filled to react. After the reaction is completed, it is cleaned in a light-proof condition, and then dried to obtain a hydrolyzed and modified porous PtBuMA carrier; (4) Preparation of porous organic carrier modified PtBuMA loaded nZVI: Weigh iron salt, polyethylene glycol, and the hydrolyzed modified porous PtBuMA carrier obtained in step (3), and mix them evenly with deionized water. After ultrasonication, add anhydrous ethanol and introduce nitrogen. After stirring, add NaBH4 aqueous solution dropwise. Continue the reaction after the addition. After the reaction is completed, centrifuge the obtained black particles, wash them, and freeze-dry them to obtain porous organic carrier modified PtBuMA loaded nZVI, which is referred to as PtBuMA-nZVI.
2. The method for preparing the porous organic carrier PtBuMA loaded nZVI adsorbent according to claim 1, characterized in that: In step (1), the initiator is benzoyl peroxide; the crosslinking agent is trimethylolpropane triacrylate, the pore-forming agent is toluene, the emulsifier is PEG-PPG-PEG; and the stabilizer is N,N-dimethylaniline.
3. The method for preparing the porous organic carrier PtBuMA loaded nZVI adsorbent according to claim 2, characterized in that: The amount of the crosslinking agent is 30%-65% of the mass of tert-butyl methacrylate; the amount of the pore-forming agent is 50%-170% of the mass of tert-butyl methacrylate; and the amount of the emulsifier is 12%-18% of the mass of tert-butyl methacrylate.
4. The method for preparing the porous organic carrier PtBuMA loaded nZVI adsorbent according to claim 1, characterized in that: In step (2), the initiator is ammonium persulfate; the dispersant is polyvinyl alcohol; the crosslinking agent is tetramethylethylenediamine; the mass dosage relationship of polyvinyl alcohol, ammonium persulfate and tetramethylethylenediamine is 0.5-1:1:0.8-1; the volume ratio of deionized water in step (2) to the aqueous phase in step (1) is 50-150:10; and the ammonium persulfate is 5-10% of the mass of tert-butyl methacrylate.
5. The method for preparing the porous organic carrier PtBuMA loaded nZVI adsorbent according to claim 1, characterized in that: In step (3), the volume ratio of trifluoroacetic acid to dichloromethane is 1:
10.
6. The method for preparing the porous organic carrier PtBuMA loaded nZVI adsorbent according to claim 1, characterized in that: In step (4), the mass ratio of FeSO4·7H2O to PEG and the modified PtBuMA carrier is 5:2.5:
2.
7. A porous organic carrier PtBuMA loaded with nZVI adsorbent prepared according to the method of any one of claims 1 to 6.
8. Use of the porous organic carrier PtBuMA loaded with nZVI adsorbent prepared according to the method according to any one of claims 1 to 6 in removing Cu(II), Zn(II) and As(III) ions from water.
Citation Information
Patent Citations
Novel method for preparing load nano zero valent iron
CN102205419A
